Representation Theorems for Integrated Semigroups - Vugdalić, Ramiz (Sarajevo Journal of Mathematics, 2024)
In this paper ( S(t)) _t≥ 0 is an exponentially bounded integrated semigroup on a Banach space X, with generator A. We present some relations between an integrated semigroup and its generator A, or its resolvent. 2000 Mathematics Subject Classification. 47D60, 47D62